2011
DOI: 10.1073/pnas.1101306108
|View full text |Cite
|
Sign up to set email alerts
|

Trichome-derived O -acyl sugars are a first meal for caterpillars that tags them for predation

Abstract: Plant glandular trichomes exude secondary metabolites with defensive functions, but these epidermal protuberances are surprisingly the first meal of Lepidopteran herbivores on Nicotiana attenuata. O-acyl sugars, the most abundant metabolite of glandular trichomes, impart a distinct volatile profile to the body and frass of larvae that feed on them. The headspace composition of Manduca sexta larvae is dominated by the branched chain aliphatic acids hydrolyzed from ingested O-acyl sugars, which waxes and wanes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
155
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(162 citation statements)
references
References 39 publications
6
155
0
1
Order By: Relevance
“…The prey assessment behavior of this predator indicated that it was deterred by a factor related to the larvae's external surface or its headspace. Recently, we discovered that M. sexta larvae emit branched chain aliphatic acids by hydrolyzing the O-acyl sugars that they acquire from the glandular trichomes of N. attenuata (37); this motivated us to explore how larvae might externalize a fraction of their ingested nicotine. As we were budgeting the nicotine flux through the larvae, we found that CYP-silenced larvae had lower hemolymph-and higher frass-nicotine levels, so we examined the dynamics of nicotine in the hemolymph after switching larvae from or to the foliage of nicotine-containing plants.…”
Section: Discussionmentioning
confidence: 99%
“…The prey assessment behavior of this predator indicated that it was deterred by a factor related to the larvae's external surface or its headspace. Recently, we discovered that M. sexta larvae emit branched chain aliphatic acids by hydrolyzing the O-acyl sugars that they acquire from the glandular trichomes of N. attenuata (37); this motivated us to explore how larvae might externalize a fraction of their ingested nicotine. As we were budgeting the nicotine flux through the larvae, we found that CYP-silenced larvae had lower hemolymph-and higher frass-nicotine levels, so we examined the dynamics of nicotine in the hemolymph after switching larvae from or to the foliage of nicotine-containing plants.…”
Section: Discussionmentioning
confidence: 99%
“…mortality on hemi-ir LOX2 jumped to 70% in the fourth and semi-final larval instar, this was likely due to predation by whiptail lizards ( Cnemidophorus spp.) which were present on the field plot: these lizards predate late-instar Manduca and are attracted to short-chain fatty-acid volatiles produced by the larvae due to ingestion of acyl sugars in plant trichomes (Stork et al, 2011; Weinhold and Baldwin, 2011).
10.7554/eLife.00007.014Figure 9.Cumulative mortality of Manduca spp.
…”
Section: Resultsmentioning
confidence: 99%
“…In Solanum lycopersicum , for example, herbivore movement ruptures glandular trichomes and elicits the expression of JA-mediated defense genes even prior to leaf damage [7]. In the Nicotiana tabacum-Manduca sexta system, glandular trichomes have also been shown to release volatiles following caterpillar damage that are attractive to predators [9]. In contrast, non-glandular trichomes are thought to act primarily as mechanical barriers that restrict herbivore movement and thereby prevent feeding damage [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, two commonly cultivated species, Solanum lycopersicon (tomato) and Nicotiana tabacum (tobacco), have multiple types of glandular trichomes [7,9,13], whereas the common non-domesticated weeds Solanum elaeagnifolium and Solanum carolinense are devoid of any glandular trichomes, but have a dense mat of non-glandular stellate trichomes [3,5,14], (Figure 1). Here using multiple species from Solanaceae, we examined the effects of trichome type X M. sexta larval instar on feeding initiation.
10.1080/19420889.2018.1486653-F0001Figure 1.(a) Trichome morphology of S. eleaegnifolium.
…”
Section: Introductionmentioning
confidence: 99%